Self-regulated learning among teacher education students - Muwonge, Charles Magoba; Schiefele, Ulrich; Ssenyonga, Joseph; Kibedi, Henry (Journal of Psychology in Africa, 2017)
Effective learning requires both skill and will on the part of the learner (Zusho, Pintrich, & Coppola, 2003) Skill and will in learning is premised on use of self-regulation strategies (Zimmerman, 2000) As applied to learning, selfregulation refers to the degree to which students are active participants in their own learning (Zimmerman, 2008) Aspects of self-regulation, such as motivational beliefs of self-efficacy, control of learning, task value orientation, and self-monitoring (metacognition) influence learning outcomes (Zimmerman, 2000) Previous studies have indicated that the relationship between motivational beliefs and metacognition is mediated by students’ achievement goals (Diseth, 2011; Liem, Lau, & Nie, 2008), which implies that one’s achievement goals have effects on his/her metacognition (Barzegar, 2012; Diseth, 2011) Understanding the interplay between attributes of students’ motivational beliefs and learning is vital to instructional design The present study examined the extent to which self-efficacy, task value, and control of learning beliefs predict metacognitive learning skills among Ugandan teacher education students
Motivational beliefs influence on the use of metacognition
Keywords: metacognition; motivational beliefs; motivated strategies for learning questionnaire; teacher education students